Fluid mechanics and heat transfer : advances in nonlinear dynamics modeling - Hariri Asli, Kaveh; Aliyev, Soltan Ali Ogli (Apple Academic Press, 2015)
This valuable new book focuses on new methods and techniques in fluid mechanics and heat transfer in mechanical engineering. The book includes the research of the authors on the development of optimal mathematical models and also uses modern computer technology and mathematical methods for the analysis of nonlinear dynamic processes. It covers technologies applicable to both fluid mechanics and heat transfer problems, which include a combination of physical, mechanical, and thermal techniques. The authors develop a new method for the calculation of mathematical models by computer technology, us.